Peran Sistem Informasi Manajemen Puskesmas (Simpus) Dalam Meningkatkan Pelayanan Kesehatan di Puskesmas Ciparay - Susilawati; Fitria, Idha Jalilah (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
SIMPUS promotes more structured and faster patient data management, reduces the risk of human error, and improves communication and coordination among health care professionals. Features such as notifications and electronic medical documents contribute to improving data accuracy and speed of access to information. However, the implementation of SIMPUS also faces challenges such as lack of personnel training and infrastructure limitations. This study recommends more in-depth training, development of more specific SIMPUS features, and optimization of SIMPUS benefits to improve the quality of health services at Ciparay Health Center.